2021
DOI: 10.1177/14680181211012946
|View full text |Cite
|
Sign up to set email alerts
|

Social resilience and welfare systems under COVID-19: A European comparative perspective

Abstract: COVID-19 and the corresponding economic lockdown and income loss for large segments of population was something unexpected for all European countries, and their welfare systems were not prepared to protect their citizens from such threats. Social resilience is becoming used in disaster risk analysis, and preferred to that of vulnerability, to refer the ability of the social entities to respond to such challenges, enabling them to cope and adjust to adverse events. It has been more recently used in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 10 publications
1
34
0
4
Order By: Relevance
“…Regarding the current context, rating agencies that have focused on the economic and financial growth of the northern countries model have predicted negative scenarios in the risk assessment of sovereign debts in 2021, which are due to the budgetary effort required to finance recovery programs in countries such as Greece, Italy, Portugal, and Spain (Abreu 2020;Jimeno and Ruiz 2021). At the beginning of the pandemic, national governments responded differently to address the consequences of this crisis (Martín and Román 2021b), though there was a concern in southern European countries to maintain the well-being of citizens and protect society and the economy (Pereirinha and Pereira 2021). For , the State has taken on a central role worldwide in the fight against the pandemic, which has brought with it political and legal difficulties as well as financial, social, and economic issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the current context, rating agencies that have focused on the economic and financial growth of the northern countries model have predicted negative scenarios in the risk assessment of sovereign debts in 2021, which are due to the budgetary effort required to finance recovery programs in countries such as Greece, Italy, Portugal, and Spain (Abreu 2020;Jimeno and Ruiz 2021). At the beginning of the pandemic, national governments responded differently to address the consequences of this crisis (Martín and Román 2021b), though there was a concern in southern European countries to maintain the well-being of citizens and protect society and the economy (Pereirinha and Pereira 2021). For , the State has taken on a central role worldwide in the fight against the pandemic, which has brought with it political and legal difficulties as well as financial, social, and economic issues.…”
Section: Introductionmentioning
confidence: 99%
“…For , the State has taken on a central role worldwide in the fight against the pandemic, which has brought with it political and legal difficulties as well as financial, social, and economic issues. Grasso et al (2021) considered that the consequences of COVID-19 in European societies are limited basic social and political rights, exponentiating social inequalities and weakening the well-being of citizens, including women, migrants, the elderly, caregivers, and the homeless people (Organisation for Economic Co-operation and Development 2020; United Nations 2020a; Eurofound 2021; Pereirinha and Pereira 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the effects of the 2008 crisis are still present because the Portuguese Social Security System has not fully recovered from the last financial and economic crisis [25]. Therefore, we are facing a lower capacity of social protection in the pandemic context to deal with poverty, low income, unemployment, and precarious work [61].…”
Section: Discussionmentioning
confidence: 99%
“…Given the pandemic situation and the necessity to enforce lockdowns, most EU countries introduced income replacement and/or short-term work schemes as well as a range of other social policy measures to support the population in adaption to the disruptions of work and family lives, leading to high budget deficits (Eichhorst et al 2020 ; Pereirinha and Pereira 2021 ; Seemann et al 2021 ). Thus, the first major initiative of the European Commission in the context of the COVID-19 crisis, on 20 March, was to propose the activation of the general escape clause of the Stability and Growth Pact (SGP).…”
Section: Towards the Ngeumentioning
confidence: 99%
“…National political responses have posed challenges to democracy and to democratic institutions (Goetz and Martinsen 2021 ), while the economic effect of the COVID-19 pandemic has, at least partially, been cushioned by Europe’s welfare states. At the same time, the pandemic has also led to changes in labour markets and welfare systems (Béland et al 2021 ; Pereirinha and Pereira 2021 ; Seemann et al 2021 ). The EU level response, after an initial lag, showed that the heads of state and government, despite different political interests, were able to reach an agreement on a common EU fund, Next Generation EU (NGEU), intended to support member states in shifting to a digitalized and green growth model (de la Porte and Jensen 2021 ; Ladi and Tsarouhas 2020 , Schmidt 2021 ).…”
Section: Introductionmentioning
confidence: 99%